(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the phonetic classification of consonants based on the type of obstruction created during articulation and the degree of noise produced in the speech process. The research explores the fundamental principles underlying consonant categorization in phonetics, analyzing how different articulatory mechanisms create distinct sound patterns and acoustic characteristics. Through systematic examination of obstruent and sonorant categories, this paper investigates the relationship between articulatory processes and acoustic output in consonant production.